MERAJUT KETERAMPILAN BERPIKIR KRITIS, KOLABORASI, DAN KETERAMPILAN SOSIAL SISWA SEKOLAH DASAR MENGGUNAKAN MODEL PEMBELAJARAN SINERGI - Muhammad Rizqy Ramadhani; Akhmad Riandy Agusta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve student activity, critical thinking skills, collaboration skills, social skills, and student learning outcomes. This type of research applies Classroom Action Research conducted in 3 meetings. The subjects of this study were 17 fifth-grade students of SDN Sungai Lakum 1. Research findings indicate that student activity has developed to be very active. Students' critical thinking skills, collaboration skills, and social skills have developed to be highly skilled. This has a positive effect on improving student learning outcomes so that they meet the completion criteria.